Toxicity profile of repeated doses of PEG‐asparaginase incorporated into a pediatric‐type regimen for adult acute lymphoblastic leukemia. (25th June 2015) - Aldoss, Ibrahim; Douer, Dan; Behrendt, Carolyn E.; Chaudhary, Preeti; Mohrbacher, Ann; Vrona, Janice; Pullarkat, Vinod
Abstract: Despite having been long regarded as too toxic for adult patients, pediatric‐like regimens containing L‐asparaginase have resulted in improved outcomes for adults with acute lymphoblastic leukemia (ALL). To characterize the spectrum of toxicity of repeated doses of polyethylene glycolated‐asparaginase (PEG‐asp) in adults, we reviewed all doses (2000 IU/m 2 ) administered as part of a pediatric‐inspired regimen in adult ALL at our center. Subjects aged 18–60 yr with ALL ( n  = 152, 69.1% male) contributed 522 dose cycles to the study. Hepatotoxicity was the most common adverse event: grades 3–4 transaminitis and hyperbilirubinemia occurred in 53.9% and 23.7% of subjects, respectively. Hepatotoxicity was reversible; no cases of fulminate hepatic failure were observed. Other toxicities affecting at least 5% of subjects were grades 3–4 triglyceridemia in 50.9%, hypofibrinogenemia (<100 mg/dL) in 47.9%, clinical pancreatitis in 12.6%, venous thromboembolism in 11.2%, allergic reaction in 7.2%, and any grade bleeding in 5.3%. PEG‐asp was always discontinued after grades 3–4 pancreatitis or allergic reaction. Otherwise, toxicities did not preclude administration of additional cycles of the drug. Our results suggest that repeated PEG‐asp dosing is safe in adults aged 18–60 yr, even after occurrence of a drug‐related toxicity.